The Experience of Doctoral Nursing Candidate in Writing Publication in Journal - Amar Akbar; Tiraporn Junda (Faculty of Nursing, Universitas Jember, 2020)
Graduates of PhD nursing programs are expected to produce complex genres of writing such as abstracts, research grants, manuscripts for publication, and dissertations. Research evidence shows a wide range of variability in writing among doctoral nursing students, and these variations may become more profound when exposed to complex genres. the objective of this study to explore the experience of PhD candidate in writing publication in high indexed journal. This case study used depth interview, semi structured question, Interview conducting in English, recorded voice used for transcribing data in 2 respondents from doctoral nursing candidate in Bangkok Thailand comes from Mahidol university and Chulalongkorn university. Participants’ criteria for this study are: 1) Doctoral candidate with minimum 1 publication in high indexed journal (Scopus/ ISI Thompson) 2) Doctoral nursing students that study in Thailand 3) Pass Qualifying Exam. Data analysis used modification Benner’s methods use in this study. This study exposing three themes. Theme 1: Strategies for publish. Theme 2: Support for publishing journal. Theme 3: two ways Communication with journal editors and public. Introduce scholarly writing at the undergraduate level and reinforce across the nursing education continuum, provide students with examples of quality scholarly writing, encourage student to connect with writing mentors (peers, colleagues, family, editor, faculty) are main recommendation for postgraduate student for increasing high level publication of nursing students.